Maternal incarceration increases the risk of self-harm but not suicide: a matched cohort study - Craig Cumming; Megan F. Bell; Leonie Segal; Matthew J. Spittal; Stuart A. Kinner; Susan Dennison; Sharon Dawe; David B. Preen (Cambridge University Press, 2023)
Abstract Aims Children of incarcerated mothers are at increased risk of experiencing multiple adversity such as poverty, mental illness and contact with child protection services (CPS), including being taken into out of home care (OOHC). However, little is known about whether these children are at increased risk of suicide or self-harm compared to children not exposed to maternal incarceration or about the factors that may contribute to this. We aimed to investigate differences in the risk of suicide and self-harm between children exposed to maternal incarceration and those not exposed and examine how socio-demographic factors, maternal mental illness and CPS contact (with or without OOHC) may affect these outcomes. Methods We used a retrospective matched cohort study design, comparing 7674 children exposed to maternal incarceration with 7674 non-exposed children. We used multivariable Cox proportional hazards regression to compare the risk of suicide and self-harm between exposed and non-exposed groups, controlling for geographical remoteness, CPS contact and maternal mental illness. Results There was no significant difference in the rate of suicide (rate ratio [RR] = 1.49; 95% confidence interval [CI]: 0.78, 2.87) or risk of suicide (adjusted hazard ratio [aHR] = 0.92; 95% CI: 0.43, 1.96) between the two groups. However, the exposed group had a significantly higher rate of self-harm (RR = 2.83; 95% CI: 2.50, 3.21) and a significantly higher risk of self-harm (aHR = 1.74; 95% CI: 1.45, 2.09) compared to those non-exposed. CPS contact with or without OOHC was independently associated with an increased risk of self-harm for both groups. Conclusion Children exposed to maternal incarceration are at an increased risk of self-harm and should be prioritized to receive targeted, multimodal support that continues after the mother's release from prison. The association between CPS contact and self-harm warrants further research.